Investigating Ṣiddiq’s Mediating Effect on Enhancing Quality of Local Ready-To-Eat Culinary Products - Herwin, Herwin; Razak, Syaparuddin; Fahrika, A. Ika (Al-Infaq: Jurnal Ekonomi Islam, 2025)
This study aims to examine the role of Ṣiddīq (honesty) in strengthening local product development through the implementation of Islamic business ethics. Specifically, it analyzes the influence of Islamic Value Commitment, Product Information Transparency, and Business Social Responsibility on the development of local ready-to-eat food products, both directly and through the mediating role of Ṣiddīq. This research employs a quantitative explanatory method using a survey of local culinary entrepreneurs. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings indicate that Islamic Value Commitment, Product Information Transparency, and Business Social Responsibility play an important role in fostering Ṣiddīq among business actors. Furthermore, Ṣiddīq mediates ethical values and transparency, leading to improved product quality, enhanced consumer trust, and increased competitiveness of local products, thereby supporting sustainable local product development.